A Study Of The Relationship Between Fear Of Success And Burnout Among Working Women In Iranian Public Schools - Motaghi-Pishe, Mohammad Hossein (Asian Academy of Management (AAM), 2008)
Fear of success is derived from lack of trust and confidence in one's own personality. To be in doubt of one's self and to be anxious about other's expectations, exists constantly in the thought and behavior of working women. This, on its own, is a great source of anxiety and sets the foundation of continuous job stress. Burnout is a response to chronic job stress. It is a gradual erosion and feeling of failure, and being worn out. This paper aims to investigate the relationship between fear of success and burnout among working women in Iranian public schools. Moreover, it examines whether fear of success and burnout are related to some demographic characteristics such as age, years of service, marital status, academic background and organizational rank. The results reveal that fear of success and burnout in women working in public schools are correlated; but there are no significant differences in levels of fear of success and/or burnout relative to demographic factors.